(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
In the International Journal of Physics and Astronomy [1] a formula for calculation of dark energy was developed [1]. It is: Ed = (h/tp2) tu (1.2) In the Journal of Physics and Astronomy The Foundations of a Dark Energy Theory was mentioned for the first time in my article Commentary about Calculation of Dark Energy and Dark Matter [2] In the article which is presented here, the Theory of Dark Energy is now completed and a physical-mathematical and theoretical derivation of the formula [1] is provided. This provides physical-mathematical and theoretical sopport for the formula [1] previously developed using a simple three-sentence operation.